2021
DOI: 10.1111/jocd.13995
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of triple wavelength laser hair reduction in skin types IV to V

Abstract: Background Laser hair reduction is one of the most common laser procedures in dermatology. Laser systems available are Ruby at 694 nm, Alexandrite (755 nm), Diode (810nm), and Nd:YAG (1064 nm). Recently, devices presenting a combination of wavelengths have shown to produce high effective hair reduction with no related risks. This study was conducted with the Soprano Ice Platinum (Alma Lasers, GMBH, Germany) that emits a combination of three wavelengths at 755, 810, and 1064 nm in a single pulse. Aims To establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…All the reported side effects were transient and resolved within 2 days of onset. Furthermore, Raj Kirit et al 12 reported 76% hair reduction in the bikini area within 6 treatment sessions, and no adverse events were recorded throughout the study. The current study's results are comparable to those of previous similar studies.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…All the reported side effects were transient and resolved within 2 days of onset. Furthermore, Raj Kirit et al 12 reported 76% hair reduction in the bikini area within 6 treatment sessions, and no adverse events were recorded throughout the study. The current study's results are comparable to those of previous similar studies.…”
Section: Discussionmentioning
confidence: 90%
“…This study presents the results of thirty subjects treated with combined laser wavelengths in the axilla and bikini line. Very few studies assessed hair removal in those area 12,13 . Khoury et al 13 showed 67.1 ± 15.1% of hair reduction in the axillary area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that laser device with combination of wavelengths produces effective results in hair reduction without significant increase in risks. [11,12] Triple wavelength laser combines the synergy of three wavelengths 1064, 810 and 755 nm. Out of these three, 1064 and 810 nm have potential for deep penetration and hence focus on darker skin tones.…”
Section: Evidence For Triple Wavelength Laser In Hair Removalmentioning
confidence: 99%
“…Out of these, one study is prospective and other is retrospective. Kirit et al [11] have recently published their results of investigator initiated prospective study evaluating efficacy and safety of triple wavelength laser for hair reduction in 25 adult patients with skin types IV and V. e investigators used the Soprano Ice Platinum (Alma Lasers, GMBH, Germany) with the combination of three wavelengths at 755, 810, and 1064 nm. ese three wavelengths are emitted in a single pulse.…”
Section: Evidence For Triple Wavelength Laser In Hair Removalmentioning
confidence: 99%